Multivariate analysis of factors influencing the effect of radiosynovectomy - Farahati, J.; Schulz, G.; Wendler, J.; Körber, C.; Geling, M.; Kenn, W.; Schmeider, P.; Reidemeister, C.; Reiners, Chr. (Nuklearmedizin - NuclearMedicine, 2002)
Objective: In this prospective study, the time to remission after Radiosynovectomy (RSV) was analyzed and the influence of age, sex, underlying disease, type of joint, and duration of illness on the success rate of RSV was determined. Methods: A total number of 57 patients with rheumatoid arthritis (n = 33) and arthrosis (n = 21) with a total number of 130 treated joints (36 knee, 66 small and 28 medium-size joints) were monitored using visual analogue scales (VAS) from one week before RSV up to four to six months after RSV. The patients had to answer 3 times daily for pain intensity of the treated joint. The time until remission was determined according to the Kaplan-Meier survivor-ship function. The influence of the prognosis parameters on outcome of RSV was determined by multivariate discriminant analysis. Results: After six months, the probability of pain relief of more than 20% amounted to 78% and was significantly dependent on the age of the patient (p = 0.02) and the duration of illness (p = 0.05), however not on sex (p = 0.17), underlying disease (p = 0.23), and type of joint (p = 0.69). Conclusion: Irrespective of sex, type of joint and underlying disease, a measurable pain relief can be achieved with RSV in 78% of the patients with synovitis, whereby effectiveness is decreasing with increasing age and progress of illness.
Keywords: Radiosynovectomy; multivariate analysis; rheumatoid arthritis; arthrosis; synovitis